2023
DOI: 10.1021/acsomega.2c04569
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean–Wheat Intercropping Can Control the Occurrence of Faba Bean Fusarium Wilt by Alleviating the Inhibitory Effect of Benzoic Acid on Disease Resistance Metabolism and the Expression of Resistance Genes

Abstract: Background: Continuous cropping leads to the accumulation of autotoxic substances in faba beans, which limits their global production. Intercropping is widely used to alleviate these problems. Aim: This study aims to explore the important role of Fusarium oxysporum f. sp. fabae (FOF) and benzoic acid stress in enhancing the occurrence of faba bean Fusarium wilt and the potential mechanism of faba bean−wheat intercropping to control the occurrence of this disease. Methods: We analyzed the pathogenic mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Wang et al (2023) reported that stress resulting from the treatment of poplar with the allelochemical para‐hydroxybenzoic acid resulted in increased expression of proteins associated with secondary metabolite biosynthesis, energy supply, and antioxidant defense. In the field, plants encounter combinations of stressors due to synergistic interactions between pathogens and autotoxic substances instead of individual stressors from different sources (Zheng et al, 2023). In the present study, a comparison of monocropping and FOF inoculation (M + F) with the M + F + C group showed the upregulation of six proteins in the latter, which were found to be mostly involved in carbohydrate metabolism and energy‐associated and cytoplasmic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2023) reported that stress resulting from the treatment of poplar with the allelochemical para‐hydroxybenzoic acid resulted in increased expression of proteins associated with secondary metabolite biosynthesis, energy supply, and antioxidant defense. In the field, plants encounter combinations of stressors due to synergistic interactions between pathogens and autotoxic substances instead of individual stressors from different sources (Zheng et al, 2023). In the present study, a comparison of monocropping and FOF inoculation (M + F) with the M + F + C group showed the upregulation of six proteins in the latter, which were found to be mostly involved in carbohydrate metabolism and energy‐associated and cytoplasmic functions.…”
Section: Discussionmentioning
confidence: 99%